Annual_ice_comb - Christie, Katherine; Hollmen, Tuula; Flint, Paul; Douglas, David; Christie, Katherine (Dryad Digital Repository, 2018)
Projected sea ice data (number of days with >95% sea ice cover and <15% sea ice cover) for the Spectacled Eider core wintering area. Data from Global Circulation Models were downloaded from archives of CMIP5 GCM outputs (see Table S3 for a list of models).